Inhalable locust bean gum microparticles co-associating isoniazid and rifabutin: therapeutic assessment in a murine model of tuberculosis infection - Grenha, Ana (2021)
Tuberculosis is a leading cause of death worldwide. Although the development of new antimycobacterial drugs is an obvious and necessary strategy to address the disease, improving the therapeutic performance of drugs already approved constitutes a valuable alternative approach. As the lung is the most affected organ, where M. tuberculosis is able to survive and proliferate, the direct pulmonary delivery of antitubercular drugs comprises a highly promising therapeutic strategy. In this work, spray-dried locust bean gum (LBG) microparticles were used to deliver a combination of two first line antitubercular drugs, isoniazid (INH) and rifabutin (RFB), to the alveolar zone, where macrophages hosting the bacteria reside. LBG is expected to mediate favoured macrophage uptake of microparticles, leading to enhanced therapeutic effect. The therapeutic effect of LBG/INH/RFB microparticles was evaluated in a murine model infected with M. tuberculosis, strain H37Rv and compared with oral co-therapy of INH and RFB in the free form. The pulmonary administration of LBG/INH/RFB microparticles 5 times per week was the only treatment schedule that provided negative growth index values in lung (-0.22), spleen (-0.14) and liver (-0.26) even using a lower therapeutic dose for both antibiotics. For the control group, the respective values were +1.95, +0.75 and +0.96.